2021
DOI: 10.1007/s10072-021-05470-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on potential differentially expressed genes in stroke by bioinformatics analysis

Abstract: Stroke is a sudden cerebrovascular circulatory disorder with high morbidity, disability, mortality, and recurrence rate, but its pathogenesis and key genes are still unclear. In this study, bioinformatics was used to deeply analyze the pathogenesis of stroke and related key genes, so as to study the potential pathogenesis of stroke and provide guidance for clinical treatment. Gene Expression profiles of GSE58294 and GSE16561 were obtained from Gene Expression Omnibus (GEO), the differentially expressed genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…CLEC4D is one of the hub genes that is differentially expressed between IS patients and controls 21 and may be involved in mir-27a-3p−CLEC4D regulation. 22 In addition, it was previously found that CLEC4D and CD163 are immune biomarkers for IS, and these genes were used to construct classification models based on a neural network algorithm. This also revealed that CLEC4D is strongly correlated with the proportion of neutrophils in sera of IS patients.…”
Section: ■ Discussionmentioning
confidence: 99%
“…CLEC4D is one of the hub genes that is differentially expressed between IS patients and controls 21 and may be involved in mir-27a-3p−CLEC4D regulation. 22 In addition, it was previously found that CLEC4D and CD163 are immune biomarkers for IS, and these genes were used to construct classification models based on a neural network algorithm. This also revealed that CLEC4D is strongly correlated with the proportion of neutrophils in sera of IS patients.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[39] hsa-miR-27a-3p and hsa-miR-335-5p were crucial in IS, whereas hsa-miR-34a-5p was crucial in MI. [40,41] The above information may reveal some unique mechanisms underlying the diseases, suggest new disease markers, and provide a possible basis for predicting IS and MI, as well as identify potential therapeutic targets. The prediction of drugs may have a role in disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin subunit alpha M (ITGAM) gene encodes Integrin αM (CD11b), which might promote the development and progression of abdominal aortic aneurysm via mediating the adhesion of endothelial cells and the transendothelial migration of circulating monocytes/macrophages (53). C-type lectin domain family 4 member D (CLEC4D) and mast cell expressed membrane protein 1 (MCEMP1) are identified to be potential prognostic and diagnostic biomarkers for ischemic stroke (54,55). Solute carrier family 2 member 3 (SLC2A3) is reported to correlate with platelet aggregation (56), syndromic congenital heart disease (57), and chronic thromboembolic pulmonary hypertension (58).…”
Section: Discussionmentioning
confidence: 99%